T-type calcium channels and thalamocortical rhythms in sleep: A perspective from studies of T-type calcium knockout mice - 이정륜; 신희섭 (Bentham Science Publishers, 2007)
Sleep is characterized by synchronized electrical activities of the thalamocortical network, which can be identified as the-EEG oscillations during sleep. T-type calcium channels have been implicated in the occurrence of sleep waves, and burst firings in the thalamic neurons driven by these channels are known to be essential for modulation of sleep rhythms. Studies showed that α1G T-type calcium channel knockout mice had defects in sleep waves such as lack of delta oscillations (1-4 Hz) and alteration of sleep spindles (7-15 Hz), which are known to be modulated by T-currents in the thalamus. The mutation also affected the sleep-wake transition, thus resulting in decreased NREM sleep and increased sleep disturbance. These findings support the idea that α1G T-type calcium channels contribute to sleep waves as well as to behavioral state of sleep. ？ 2007 Bentham Science Publishers Ltd.